Effect of drinking water supplementation of different aromatic plant essential oils on performance and some blood parameters in quail breeders (coturnix coturnix japonica) - Özlem Durna Aydın (Eurasian Journal of Veterinary Sciences)
Aim: The purpose of this study is to investigate the effect of added to Mintofarm (mixture essential oil consist of mint oil, juniper oil, rosemary oil and oregano vulgare oil) added in drinking water at on performance, egg production and blood antioxidant parameters such as glutathione (GSH), superoxide dismutase (SOD) and glutathione peroxidase (GPx) catalase (CAT) enzyme activities, malondialdehyde, ceruloplasmin, albumin, total protein and globulin in quail breeders. Materials and Methods: A total of 160 quail breeders 17 weeks of aged were randomly divided into 3 groups and each group was divided into 5 subgroups. There were 60 quails in the control group and 50 quails in the other two groups. Male and female numbers were equal. Treatments were as follows: C (Control; without supplementation); M1 (0,1ml/L mintofarm supplementation in drinking water) and M2 (0,3ml/L mintofarm supplementation in drinking water). Results: It was determined that the addition of mintofarm to drinking water of quail breeders did not have a significant effect on performance, egg weight, daily egg production, CAT, ceruloplasmin, albumin, total protein, and globülin. MDA, GSH, SOD and GPx values were significantly affected by the addition of mintofarm (p<0.05). Conclusion: It has been determined that mintofarm did not affect the performance parameters, it significantly affected the oxidantantioxidant balance in quail bredeers.The use of mintofarm in quail bredeers drinking water has a protective effect against oxidative stress.